Dose assessment of 4- and 16-slice multi-detector computed tomography (MDCT) scanners. (March 2020) - Omar, R.S.; Hashim, S.; Ghoshal, S.K.; Shariff, N.D.
Abstract: This paper reports the performance of an X-ray generator and the CT dosimetry of 4- and 16-slice Multi-Detector Computed Tomography (MDCT) scanners operating in the axial mode. Two types of CT scanners were evaluated; the 4-slice Toshiba Asteion 4 Edition and the 16-slice Siemen Somatom Emotion 16. The dose estimation for the X-ray generator and the MDCT of the scanners were assessed under certain parameters (kV, mA, and exposure time) using a multi-function detector (Raysafe Unfors), and nanoDot™ OSLDs. The weighted CT Dose Index (CTDIw ) was measured using a 100 mm standard pencil beam ion chamber, and nanoDot™ OSLDs, in a 160 mm-diameter head and 320 mm-diameter body cylindrical acrylic Polymethyl-Methacrylate (PMMA) phantom (160 mm length). The CTDIw values were specified either according to the central axis or 10 mm from the 4 outer edges of the phantom. The two sizes of the phantoms based on the measurements of the CTDIw of the two CT scanners were compared. The weighted CTDIs (CTDIw ) were calculated and the CT X-ray generator performance observed. The results of the two different types of detectors were examined and compared. The deviation accuracy of the tube voltage was ±5 kV or ±5%, whichever is greater, whereas the accuracy of the tube potential (mA) was ±10%. The radiation dose (CTDIw ) for dosage under exceptional CT scanning conditions in the axial mode was observed to meet the manufacturer's guidelines (<±20%). The implementation of the CT dosimetry steps ensured patient safety and is expected to reduce future risk in the case that an estimated dose value was inappropriately administered above the relevant threshold for any routine CT examination.